RETRACTED: Activity-target methodology - a new mechanism for assessing the quality of education - Timoshek Igor (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001